2018
DOI: 10.1016/j.surfcoat.2018.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silica nanoparticles on the morphology and mechanical properties of sol-gel derived coatings

Abstract: Although corrosion resistance and mechanical properties of sol-gel coatings have been studied independently, there are limited studies that consider both collectively. However, since any form of mechanical damage could impair the protective function of the coating, it is prudent to consider the mechanical durability of coatings as well as their corrosion resistance. The present work considers the impact of silica nanoparticles on the morphology and mechanical properties of a sol-gel derived coating. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…They evaluated the electrochemical corrosion resistance of low carbon steel coated with hybrid organic-inorganic sol-gel film, made by 3-glycidoxy-propyl-trimethoxy-silane (GPTMS) and tetra-ethyl-ortho-silicate (TEOS) precursors and filled with silica or alumina nanoparticles [180]. A similar study was performed by Vivar Mora et al, which assessed the impact of silica nanoparticles on the morphology and mechanical properties of a GPTMS/TEOS sol-gel coating [186]. The authors observed that features, such as hardness, elastic modulus, brittleness and fracture toughness, were improved when the mild steel surface was treated with silica NPs, leading to a more durable and corrosion resistant coating.…”
Section: Industrial Coatingsmentioning
confidence: 99%
“…They evaluated the electrochemical corrosion resistance of low carbon steel coated with hybrid organic-inorganic sol-gel film, made by 3-glycidoxy-propyl-trimethoxy-silane (GPTMS) and tetra-ethyl-ortho-silicate (TEOS) precursors and filled with silica or alumina nanoparticles [180]. A similar study was performed by Vivar Mora et al, which assessed the impact of silica nanoparticles on the morphology and mechanical properties of a GPTMS/TEOS sol-gel coating [186]. The authors observed that features, such as hardness, elastic modulus, brittleness and fracture toughness, were improved when the mild steel surface was treated with silica NPs, leading to a more durable and corrosion resistant coating.…”
Section: Industrial Coatingsmentioning
confidence: 99%
“…They evaluated the electrochemical corrosion resistance of low carbon steel coated with hybrid organic-inorganic sol-gel film, made by 3-glycidoxy-propyl-trimethoxy-silane (GPTMS) and tetra-ethyl-ortho-silicate (TEOS) precursors and filled with silica or alumina nanoparticles [176]. A similar study was performed by Vivar Mora et al, which assessed the impact of silica nanoparticles on the morphology and mechanical properties of a GPTMS/TEOS sol -gel coating [182]. The authors observed that features, such as hardness, elastic modulus, brittleness and fracture toughness, were improved when the mild steel surface was treated with silica NPs, leading to a more durable and corrosion resistant coating.…”
Section: Industrial Coatingsmentioning
confidence: 99%
“…Due to their small size and high surface area to volume ratio, their physical and chemical properties are enhanced in comparison to their bulk state (Lisjak & Mertelj 2018). Within such small size units, the effective surface area becomes very large, owing NMs unique optical (Bhalla & Tyagi 2018), magnetic (Hu et al 2018) and mechanical properties (Vivar Mora et al 2018). In figure 7, a schematic diagram demonstrates the importance of NMs in the applications of water treatment and purification.…”
Section: Synthesis Properties and Applications Of Nanomaterials For Membrane Modificationmentioning
confidence: 99%